Provincial Solidarities: A History of the New Brunswick Federation of Labour - David Frank (Working Canadians: Books from the CCLH, 2013)
Established in 1913, the New Brunswick Federation of Labour is the second oldest provincial federation of labour in Canada. Its history began in early campaigns for workers